Current Trends in the Epidemiology and Treatment of Esophageal Cancer in South Korea - Hye Weon Kim; Seong Yong Park (Journal of Chest Surgery)
According to 2021 statistics, esophageal cancer ranked as the 18th most common cancer and the 10th leading cause of cancer-related deaths in Korea, predominantly manifesting as squamous cell carcinoma. The incidence of esophageal cancer in Korea has been on a gradual decline, while the proportion of early-stage diagnoses has increased, leading to an improvement in the 5-year relative survival rate. The Health Insurance Review & Assessment Service, reports that around 800 esophagectomy procedures are performed each year. However, due to the absence of recent updates, there is a pressing need to establish a comprehensive nationwide registry or database for esophageal cancer and esophagectomy.